Childhood Neglect and Malevolent Creativity among Emerging Adults: Exacerbating role of Light Triad Traits - Kashaf Amreen; Afreen Komal; Muhammad Faran (Research Journal of Psychology, 2025)
Early life experiences, particularly childhood neglect, can significantly influence personality traits and creative expression in adulthood. The study aimed to examine the moderating role of light triad traits between childhood neglect, and malevolent creativity among emerging adults. Using a correlational design, data were collected from N=330 participants (n=155 men, n=175 women) aged 18–25 years (M = 20.63, SD = 1.88), recruited through purposive sampling from educational institutions in Rawalpindi, Islamabad, and Abbottabad. The Childhood Trauma Questionnaire (Bernstein et al., 2003), Light Triad Scale (Kaufman et al., 2019), and Malevolent Creativity Behavior Scale (Hao et al., 2016) were used for data collection. Pearson product moment correlation analysis revealed that childhood neglect negatively correlated with light triad traits and positively correlated with malevolent creativity, while light triad traits were negatively associated with malevolent creativity. Moderation analysis revealed that light triad traits significantly moderated the relationship between childhood neglect and malevolent creativity. These findings underscore the complex psychological mechanisms linking early adverse experiences to antisocial creative expression and highlight the protective role of light triad traits in mitigating these effects. The study offers valuable insights for clinical and developmental interventions, and lays the groundwork for future research.